Thoracoscopy and talc poudrage compared with intercostal drainage and talc slurry infusion to manage malignant pleural effusion: The TAPPS RCT - Bhatnagar, R; Luengo-Fernandez, R; Kahan, BC; Rahman, NM; Miller, RF; Maskell, NA (National Institute for Health Research, 2020)
Background: There are around 40,000 new cases of malignant pleural effusion in the UK each year. Insertion of talc slurry via a chest tube is the current standard treatment in the UK. However, some centres prefer local anaesthetic thoracoscopy and talc poudrage. There is no consensus as to which approach is most effective.